Planning for Mine Closure at De Beers Consolidated Mines — An Integrated Approach - Mban, M (Mine Closure 2008: Third International Seminar on Mine Closure, 2008)
The success of the De Beers Group of Companies is closely linked to the emotional value the public attaches to the product: diamonds. Over and above meeting legal requirements, building and maintaining a good reputation is key to ensuring the sustainability of the existing mining and exploration activities, as well as securing future exploration and mining activities. The environmental and social issues linked to mine closure are our responsibility, and have the potential to impact on the company’s reputation and therefore cannot be ignored. This is particularly relevant when one considers that some of the De Beers mining operations are nearing the end of their economic lives. The De Beers South African operations vary greatly in age: some are more than a hundred years old (for example Kimberley Mines); others are new operations currently being constructed (Voorspoed Mine). The environmental and social issues associated with each mining operation are similar, but at the same time, each is unique. Having recognized this, De Beers has adopted, and is busy with, a roll out of a mine closure planning tool (developed by Anglo American plc) that aims to ensure better integration of environmental and social issues as part of the business process in line with the company’s principles and values. The paper describes the drivers for implementation of this integrated approach, the myths dispelled in adopting this process of planning for mine closure, the change in attitude towards mine closure, the challenges experienced in implementing the approach at the various De Beers operations and, as a case study, the adaptation of the mine closure planning tool for an accelerated closure of a small mine, The Oaks Mine, in Limpopo Province. The benefit of adopting such a process is that the company moves beyond legal compliance and there is a business case in appropriately planning for mine closure. Most importantly, De Beers can realize its vision in terms of leaving a positive legacy in the areas in which it operated.